Modification of Flat Burr Type Coffee Bean Grinder Mill - Arta Naomi Cristiana Simanjuntak; Achwil Putra Munir; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2015)
Milling is done to reduce size or to powder food material into a certain level of refinement to be more easily processed into other products. The aims of this research was to modify, design, build and test flat burr mill type coffee bean grinder on robusta coffee and arabic coffee. Observed parameters were the effective capacity ofthe equipment, the percentage of losses materials, and economic analysis.The results showed that the effective capacity of the equipment were 35,66 kg/hour for robusta coffee and 33,84% for arabic coffee. Losses of robusta coffee bean was 0,043% and arabic coffee was 0,032%. Losses coffee powder of robusta coffee was 4,3% and arabic coffee was 12,00%. The economic analysis was Rp. 1.074,25/kg, the average of BEP was 216.5967341 kg/year for robusta coffee and 216.7716519 kg/year for arabic coffee. The 6% NPV was Rp. 3.539.104.339,00 for robusta coffee and Rp. 3.460.116.952,00 for arabic coffee. The IRR was 46,26% for robusta coffee and 46,28% for arabic coffee. Keywords: flat burr mill, coffee, grinder, rotor, stator.